2019
DOI: 10.5430/rwe.v10n1p17
|View full text |Cite
|
Sign up to set email alerts
|

Revised Malaysian Shariah Screening: Its Impact on Islamic Capital Market

Abstract: Shariah Advisory Council (SAC) of Securities Commission (SC) formulated a new revised Shariah screening methodology of two-tier quantitative assessment for activity-based screening benchmarks and the newly-formulated financial ratio benchmarks, while the qualitative assessment remains the same. The revised methodology is an effort to expand the Islamic capital market's (ICM) international reach which is in line with the SC objectives. The objective of this paper is to examine the impact of the recent announcem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…On the contrary, the Removal of Sharia status leads to lower TPI. Lower TPI may be due to substantial selling pressure for affected stocks (Nor et al, 2019) that also suppressed the stock price after these firms lost their Sharia certification (Yazi et al, 2015), as such supported the liquidity hypothesis theory. These findings are significant at the 1% level and remain consistent in Models 7, 8 and 10, where ΔInst_Own is used instead of Inst_Own in the regression model.…”
Section: Long Term: Regression Analysismentioning
confidence: 58%
“…On the contrary, the Removal of Sharia status leads to lower TPI. Lower TPI may be due to substantial selling pressure for affected stocks (Nor et al, 2019) that also suppressed the stock price after these firms lost their Sharia certification (Yazi et al, 2015), as such supported the liquidity hypothesis theory. These findings are significant at the 1% level and remain consistent in Models 7, 8 and 10, where ΔInst_Own is used instead of Inst_Own in the regression model.…”
Section: Long Term: Regression Analysismentioning
confidence: 58%
“…It is evidently shown in the case of the withdrawal of the Shariah-compliant status of the investment company from Shariah listed to non-Shariah listed in Malaysia. Interestingly, in addition to the same finding, Nor et al (2019) found that the announcement from Shariah listed to non-listed has no significant impact on the overall return of the FBM Emas Shariah index.…”
Section: The Impact Of Snc Risk On Investmentsmentioning
confidence: 60%
“…According to Nor et al (2019), Kassim et al (2017) and Yazi, et al (2015), Shariah non-compliant financial investment of companies has affected their stock price. It is evidently shown in the case of the withdrawal of the Shariah-compliant status of the investment company from Shariah listed to non-Shariah listed in Malaysia.…”
Section: The Impact Of Snc Risk On Investmentsmentioning
confidence: 99%
“…Implications of this study may include suggestions for improvement or adjustment of regulations in the Islamic capital market (Nor, 2019). Policymakers may consider changes or clarifications in the regulatory framework to ensure more clarity regarding Islamic standards and supervisory procedures (Alaoui, 2020).…”
Section: B Regulatory Improvementsmentioning
confidence: 99%